Application and Performance Analysis of PLA in Food Packaging Materials: A Mini-Review - Song, Jialing; Wu, Peixuan; Dai, Yujia; Nie, Zihao; Chen, Hongyu; Wang, Chengming; Li, Yuanzhe (International Journal of Materials Science and Technology Studies, 2024)
Compared with traditional petroleum plastics (such as polyethylene, polypropylene and polystyrene) extracted from corn starch (PLA), it has significant advantages, especially in terms of strength, moisture -proof and biodegradability. Essence Due to its excellent performance, polymapilic acid has been commercialized in the field of textiles and packaging. This review aims to explain the difference between the performance of biodegradable packaging and traditional petroleum base materials in the application of biochemical packaging packaging and traditional petroleum base materials, and conduct critical analysis. The performance of breathability and antibacterial ability focused on the modification of polymapilic acid for food preservation packaging. Overall, polystrackic acid as a promising sustainable food packaging substitute has a biochemical and degradable environmental friendship, but it is necessary to further study to solve its production cost and performance restrictions. This article will take polystrackic acid (PLA) as an example to explain the performance advantages of biodegradable packaging and application and future development.